Tracing the Sources: A comparative content analysis of Belgian health news. (16th March 2018) - Stroobant, Joyce; De Dobbelaer, Rebeca; Raeymaeckers, Karin
Abstract : This article explores health journalists' sourcing patterns in the Dutch-speaking part of Belgium across a range of different media including newspapers, magazines, radio, television and online health news websites. A cross-sectional quantitative content analysis of health news items collected in February 2015 ( N = 981) was established to examine the number and origin (e.g. industry, citizens, experts) of sources ( N = 1998) mentioned in health news stories with particular attention paid to differences across various media types. Despite recent claims of media convergence, cross-media comparisons are scarce and, for a specialized beat such as health, nonexistent. The key findings of this study indicate that ordinary citizens and academic experts constitute the two largest source categories. The small share of industry-related sources confirms journalists' skeptical attitude towards content provided by the industry. But on closer inspection, large differences can be observed across various media types. On the one hand, ordinary citizens occur with relatively high frequency on television but hardly make an appearance in online news items. Academic sources, on the other hand, are dominant online but nearly absent in television news items. In sum, this analysis demonstrates that health journalists' source uses differ across various media platforms.